PHYSICAL PREPARATION FOR ICE HOCKEY WITH UNTRADITIONAL MEANS - Kisis, Igors; Svarinskis, Mihails; Kaupuzs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The data from empirical researches in sport training methodology show that leading factors, which define hockey player’s special physical preparation is a strength and aerobic capacity of muscles groups that realize movement on ice. Aim of the research: improvement of physical preparation training process in ice hockey, using “Slide board” equipment. Subjects of the research: youth age group (U17) of the ice hockey team who were implemented eight modified “Slide board” exercises in the training process during 8 weeks. The results of experimental group show significant improvement (α<0.05) in “Acceleration and breaking skating 5x54m” test. Using routine of exercises with “Slide Board” equipment and applying repetition method during overall physical preparation period time, experimental group participants had been achieved an effective increase in special strength endurance than control group, which used training program based on previous season exercises and applied circle training after interval extensive method.